Effect of climate change on water resources management: a review of the literature - João Manuel Felisberto Chivambo; Fernando Bonde; Idalencio Chichava; Juma Abuchir; Simões Cuinica; Valdemiro Muhala (Urban, Planning and Transport Research)
Water security and climate change are interconnected, bringing new risks to population and ecosystems, where changes in precipitation patterns and evaporation are notable. This study conduct a systematic review of 40 scientific articles indexed in the Scopus database, published between 2009 and 2025, with a global analytical scope. The objective is to systematize the literature on the impacts of climate change on water resource management, identifying trends in scientific production related to mitigation and adaptation strategies. The results indicate a growing concern with freshwater scarcity caused by climate change and emphasize the urgent need for a unified global response. Efficient management tools and adaptive strategies, based on local studies and community engagement, are highlighted as essential. The findings also suggest that water governance remains a complex challenge, requiring collaboration among scientists, policymakers, and local populations, as well as institutional capacity to address changes in water availability and associated risks.